Perencanaan Kegiatan Retensi Rekam Medis di Rumah Sakit Islam Jakarta Pondok Kopi - Diva Angelita; Puteri Fannya; Deasy Rosmala Dewi; Daniel Happy Putra (Yayasan Literasi Sains Indonesia, 2024)
Medical record retention (shrinkage) is the reduction of archives through the process of sorting documents 5 years after the patient dies or the last date of treatment. This study aims to plan medical record retention activities at RSIJ Pondok Kopi to overcome the problem of file accumulation, improve the efficiency of medical record management, and support better health services. This study uses a qualitative descriptive method and is sourced from 4 informants consisting of the head of medical records and medical record officers, in attracting informants using purposive sampling techniques. In the initial observation, the Jakarta Islamic Hospital Pondok Kopi has not resumed retention of medical records for the last 4 years due to hospital policies regarding service priorities. The results of this study indicate that RSIJ Pondok Kopi already has adequate retention SOPs, but has not retained medical records since 2020. This has resulted in the accumulation of medical record files in the storage room. Based on the results of the study, it can be concluded that RSIJ Pondok Kopi needs to immediately implement medical record retention to overcome the problem of file accumulation. The retention activity plan was made as input for retention so that it can overcome the problems in the medical record unit due to not having medical record retention.